2019
DOI: 10.7759/cureus.5939
|View full text |Cite
|
Sign up to set email alerts
|

The Maverick Disease: Cystic Echinococcosis in Unusual Locations: A Ten Year Experience from an Endemic Region

Abstract: BackgroundCystic echinococcosis (CE) is a neglected tropical disease which affects more than 1 million people globally, causing a loss of 1-3 million disability-adjusted life years (DALYs) and a financial burden of US$ 3 billion annually.The two most commonly involved organs are the liver and the lungs with involvement in 75% and 5 -15% of cases respectively. The rest of the body can be involved in up to 10% of cases. In this study, we aim to explore the presentation, treatment and outcomes of CE in unusual lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“… Cerda et al. (2018) observed that the liver was the most frequently affected organ, followed by the lungs, spleen, and the mesentery, coinciding with other reports from Pakistan ( Butt and Khan, 2019 ; Khan et al., 2019 ) and elsewhere ( Kamali et al., 2018 ; Mahmoudi et al., 2019 ). However, Salem et al.…”
Section: Discussionsupporting
confidence: 83%
“… Cerda et al. (2018) observed that the liver was the most frequently affected organ, followed by the lungs, spleen, and the mesentery, coinciding with other reports from Pakistan ( Butt and Khan, 2019 ; Khan et al., 2019 ) and elsewhere ( Kamali et al., 2018 ; Mahmoudi et al., 2019 ). However, Salem et al.…”
Section: Discussionsupporting
confidence: 83%
“…5,6 Additionally, CE has been considered as a neglected tropical disease (NTD) by The World Health Organization (WHO), and it has been estimated that around 1−3 million disability cases have been reported as a result of this disease per annum. 7 Furthermore, around US $3 billion have been spent yearly because of direct and indirect effects of this disease on both humans and livestock. 8 Presently, there are several choices for the treatment of CE.…”
Section: Introductionmentioning
confidence: 99%
“…This infectious disease causes a significant public health issue worldwide, including areas of central South America, Asia, and even in Mediterranean countries . Moreover, although the infected body produces humoral immune and specific cellular responses, a persistent cohabitation of Echinococcus granulosus and has been found to be the main challenge in this disease. , Additionally, CE has been considered as a neglected tropical disease (NTD) by The World Health Organization (WHO), and it has been estimated that around 1–3 million disability cases have been reported as a result of this disease per annum . Furthermore, around US $3 billion have been spent yearly because of direct and indirect effects of this disease on both humans and livestock …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the initial diagnosis of spinal tuberculosis or spinal pyogenic infection, according to the patient’s clinical symptoms and signs, a differential diagnosis should consider spinal hydatidosis, malignancies, giant cell tumors of bone, etc. [ 8 , 9 ]. The overall incidence of spinal hydatidosis is very low, and it is more likely to be misdiagnosed and missed.…”
Section: Discussionmentioning
confidence: 99%